Effectiveness of Stock Price Prediction Models and Affecting Factors - Guo, Jiaming (International Journal of Global Economics and Management, 2024)
This paper aims to improve effectiveness of stock price prediction model in terms of factors that contain both financial and non-financial. First introduced the different models containing ARIMA, GARCH, RNN and LSTM, their pros and cons and applied cases. Then introduced financial factors including profitability, efficiency, liquidity, solvency and investment-related. Finally, the non-financial factors in terms of four aspects: Cases, Investor preference, Policies and ESG. By analyzing these factors, deriving the conclusion of in which way and how the factors will affect the effectiveness of models.